Al-Khurūj ‘alā al-Ḥākim fī al-Fiqh al-Siyāsī al-Islāmī: Dirāsah ‘alā Ma’nā al-Thawrah - Taufiqul Hadi; Mohammad Yunus Masrukhin; Siswanto Masruri; Ibnu Burdah (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
The Arab Spring emerged due to a political crisis in most Arab countries that wanted a change from dictatorial regimes to democratic systems in their countries. One of the most prominent issues that caused controversy during the revolution was the issue of al-khurūj 'alā al-ḥākim. This article aims to analyze the meaning of revolution from an Islamic political perspective by discussing the concept of al-khurūj 'alā al-ḥākim, especially towards the three terms: al-bāghī, al-khawārij and al-ḥirābah. This article clarifies the relationship between these three terms with the phenomenon of revolution in the contemporary Islamic world. This article uses a jurisprudential approach with an inductive method by extrapolating jurisprudential sources and references related to the research subject. This article concludes that the notion of revolution is not the same as the concept of al-khurūj 'alā al-ḥākim in Islamic jurisprudence. The reason is that revolution aims to change the political, social and economic reality. In contrast, khurūj is a form of resistance to the leader and does not carry out all the rights demanded of the ruler. In the present context, the redefinition of the concept of al-khurūj 'alā al-ḥākim in Islamic jurisprudence is necessary to suit the modern era.